A Survey on Helopeltis antonii Signoret Infesting Indian Almond, Terminalia catappa L. - Rakhesh, S.; Udikeri, S. S.; Hanchinal, S. G.; Mahantesh, S. T.; Naik, Chinna Babu; Prabhulinga, T.; Hurali, Sujay; Mahamed, Ashiq I.; Anvesh, Sankuratri (International Journal of Economic Plants, 2024)
Roving survey was carried in Dharwad and Belagavi districts of Karnataka between July and November, 2023 to record the incidence and damage caused by tea mosquito bug, Helopeltis antonii on Indian almond, Terminalia catappa and found that regional variations in incidence and infestation levels. Dharwad location recorded highest bug population (4 adults or nymphs 10-1 trees) with 40% of infested trees. However, Garag location recorded lowest bug population (1 adult or nymph 10-1 trees) with 10% of infested trees. Intriguingly, tea mosquito bug completes its biology on Indian almond, with an average life cycle period of 38.30±4.37 days and the range 31.5 to 43.5 days. However, egg hatching rate was 74.68% with a varied survival rate of nymphal instars and adult was recorded. In essence, this research not only provides crucial insights into incidence and damaging symptoms caused by H. antonii on Indian almond but also on biology of tea mosquito bug on T. catappa.